The use of dental service and the perception of oral health of high risk pregnant women - Saliba NA, Saliba TA, Moimaz SAS, Ros DT, (ARCHIVES OF HEALTH INVESTIGATION, 2019)
In the gestational period, some diseases and conditions such as obesity, diabetes, hypertension, syphilis, considered to be at high risk for gestation, can cause damage to oral health, on the other hand, when unsatisfactory can exacerbate or cause other conditions. This study aimed to evaluate the use dental care utilization and oral health perception of high-risk pregnant women. A crosssectional, inquiry-type research was performed with 1200 high-risk pregnant women, who received prenatal care in a specialized health care reference center. A specific form was applied during the interviews. Women in advanced pregnancy and those who were not able to answer the questions were excluded. Dental care utilization and the perception on teeth and gingiva were considered outcome variables. The data were analyzed in Epi Info 7.4.1 and Bioestat 5.3 software, at 5% significance level. The main conditions for indication of high-risk gestation were maternal age (39.08%), hypertension (11.25%) and gestational hypertension (15.65%), obesity (6.17%), dependence on legal or illegal drugs (8.83%), thyroid diseases (7.83%), diabetes (5.25%) and gestational diabetes (5.17%) and hemorrhagic syndromes (5.25%). From the total respondents, 1.00% had never been to the dentist and 40.08% had visited the dental office over 1 year ago, which was associated with age and occupation (p<0.05). From the respondents, 72.17% reported their teeth and gingiva as "fair" or "very poor", and 75.58% reported having had a toothache. The oral health perception was related to age (p=0.0156), level of education (p<0.0001), income (p<0.0001), occupation (p<0.0001), marital status (p<0.0001), and dental care utilization (p<0.0001). It was concluded that the dental care utilization by high-risk pregnant was low. Although a portion of the patients reported oral health as "fair" to "very poor", the barriers regarding dental care utilization during pregnancy need to be transposed. Descritores: High-Risk Pregnancy; Dental Care; Prenatal Care; Oral Health.